Investigating the bacterial profiles of Lactobacillus, Bifidobacterium, Actinobacteria, Fusobacterium, Firmicutes, and Bacteroides in stool samples from patients with severe depression and healthy individuals - Arbabi, Fatemeh; Shapoury, Reza; Haghi, Fakhri; Zeighami, Habib; Pirzeh, Reza (Psychoneuroendocrinology, 2024)
Depression is a multifaceted mental health disorder with complex etiology and significant global burden. Recent research indicates that the gut microbiota plays a role in the pathophysiology of depression, highlighting the potential role of specific bacterial species in influencing mood and cognitive function. In this study, we aimed to investigate the presence, copy numbers, and Ct values of selected bacterial species in stool samples from depressed patients (n=50) compared to control subjects (n=50). Our findings revealed significant differences in the abundance of Fusobacterium spp., Bifidobacterium spp., Lactobacillus spp., Bacteroidetes phylum, Firmicutes phylum, and Actinobacteria spp. between the two groups. Dysregulation of the gut microbiota, characterized by decreased presence of beneficial bacteria (e.g., Bifidobacterium spp., Lactobacillus spp.) and altered abundance of potentially pathogenic bacteria (e.g., Fusobacterium spp.), may contribute to the development or exacerbation of depression. These findings support the emerging concept of the gut-brain axis and its role in mental health. However, further research is needed to better understand the underlying mechanisms and explore the therapeutic potential of microbiota-targeted interventions for depression. Understanding the intricate interplay between the gut microbiota and depression could pave the way for novel treatment strategies and personalized approaches in mental health care. •This research has been conducted as “Investigating the Bacterial Profiles of Lactobacillus, Bifidobacterium, Actinobacteria, Fusobacterium, Firmicutes, and Bacteroides in Stool Samples from Patients with Severe Depression and Healthy Individuals”.•based on the data collected from the hospital on patients suffering from major depression and methods DNA EXTRACTION, PCR, REAL TIME PCR were used in this research.